2019
DOI: 10.1108/pr-01-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Institutional aspects of competence-based integration of retired military officers into the civilian labour market

Abstract: Purpose The purpose of this paper is to highlight systemic factors of competence-based integration of retired military officers into the civilian labour market in terms of the perspective of the institutions and institutional settings of competence involved in the formation and deployment. Design/methodology/approach This study is based on semi-structured face-to-face interviews with 25 retired military officers in Lithuania. Findings The main institutional problems and challenges of the competence-based l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
(22 reference statements)
1
11
0
Order By: Relevance
“…Apprenticeships can cater to those service leavers, who do not have the competencies required, and apprenticeships would allow the veterans to gain those skills. With some of the veterans, there is evidence of a mismatch of competencies which is found in the literature (Green, 2013;T utlys et al, 2019) and it can be argued that Building Heroes is trying to give the veterans the competencies that are desirable in the civilian world.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apprenticeships can cater to those service leavers, who do not have the competencies required, and apprenticeships would allow the veterans to gain those skills. With some of the veterans, there is evidence of a mismatch of competencies which is found in the literature (Green, 2013;T utlys et al, 2019) and it can be argued that Building Heroes is trying to give the veterans the competencies that are desirable in the civilian world.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Importantly, the Building Heroes Charity is educating building companies on the benefits of employing ex-service personnel, which is an important step in educating the civilian world on the competencies acquired during the military. As Green (2013) andT utlys et al (2019) argue the civilian world misinterprets and misunderstands military competencies but in this case Building Heroes is assisting in this understanding, and presently Davidson Homes is willing to listen.…”
Section: Military Career Transitionmentioning
confidence: 99%
“…Davis and Minnis (2017) emphasize the importance of getting a better understanding of veterans’ experience and focus on the skills that are transferable to the civilian sector. In a recent study based on semi-structured face-to-face interviews with 25 retired military officers in Lithuania, Tūtlys et al (2019) concluded that there is a lack of awareness among civilian employers of the skills and competencies that can be acquired in military service. Their findings indicated that military personnel exhibited negative feelings about their future career and skills development and that veterans tended to lack information about the skill requirements of civilian jobs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, military culture penetrates attitudes and behavior, whereas individuals report strong identification with the military [26][27][28]. The military's impact on an individual increases along the duration of the military service [29]. Based on this evidence it could be assumed that the awareness of energy criticality in the military is increasing over the years of service, as shown by research in military energy efficiency [10].…”
Section: Introductionmentioning
confidence: 99%